Isostatic hot-pressed tungsten radiation shields against gamma radiation - Daria I. Tishkevich; Stepan A. German; Anastasia A. Rotkovich; Tatiana N. Vershinina; Аliaksandr L. Zhaludkevich; Yuan Yao; Maksim V. Silibin; Ihar U. Razanau; Tatiana I. Zubar; Anastasia A. Bondaruk; M.I. Sayyed; Alex V. Trukhanov (Journal of Materials Research and Technology, 2024)
An isostatic hot-pressing technique for the fabrication of dense W samples' is presented. The samples’ microstructure and chemical content were analyzed. The most compact samples were received at 5 GPa pressure and 1500 and 2000 °C temperatures, with densities of 18.50 and 19.07 g/cm3, respectively. It has been established that high temperature exposure has a positive effect on both the microstructure and density. It is shown that as the sintering temperature increases, the porosity of the samples decreases from 32.31% to 0.94%, and their relative density increases from 67.69% to 99.06%. The crystal structure investigation revealed that all the samples contain the main body-centered cubic W phase, and the availability of the WO2 phase is observed just after the temperature of sintering increases above 1000 °C, which is confirmed by the appearance of 111 and 22-2 reflections. A study of the shielding effectiveness against gamma-radiation was carried out using the Phy-X/PSD software. A gamma-ray source of Co60 with energies of 0.8–2.5 MeV was applied for the calculations. The results were calculated for the sample with the highest density (19.07 g/cm3) and compared with the calculations for Pb. The W shielding effectiveness main parameters are determined: linear attenuation coefficient (at 0.8 MeV–1.46 cm-1), mean free path (at 2.5 MeV–1.2 cm) and half value layer (at 2.5 MeV–0.86 cm). These values turned out to be higher than for Pb, which makes shields based on W promising for use in the field of radiation protection.